GROWTH INTERDEPENDENCE AMONG INDIAN STATES: AN EXPLORATION - Shashanka Bhide, Rajesh Chadha and Kaliappa Kalirajan (Asia-Pacific Development Journal Vol. 12, No. 2, December 2005, 2005)
The objectives of this paper are to test whether there are any significant trickling down effects of economic growth across the Indian states and to identify the factors influencing the existence of such effects. Using data from 1971 to 1998, and the standard statistical test of causality, this study suggests that the transmission of growth impulses across states have been limited. The results indicate that the structure ofthe economies, the growth rates of the states and the quality of state-specific institutions appear to raise the potential for significant trickle down growth effects across states